PHYSIOCHEMICAL, PROXIMATE, AND SENSORY PROPERTIES OF UNFERMENTED AND FERMENTED SOY-CARROT BEVERAGES SWEETENED WITH SUGAR, DATE, AND HONEY - PC, Obinna-Echem; LI, Barber; RM, Uchebule (Innovare Journal of Food Sciences, 2021)
Objective: Physiochemical, proximate, and sensory properties of unfermented and fermented soy-carrot beverage sweetened with sugar, date, and honey were evaluated. Phytochemical content of soymilk, carrot juice, and their blend was also analyzed. Methods: Three sets of soy-carrot beverages were produced by homogenizing soy milk and carrot juice in a ratio of 2:1 and sweetened to 12% Brix. Each set was sweetened with sugar, date, and honey, respectively. A fourth set was unsweetened and served as control. After pasteurization, one part was fermented with pure culture of Lactobacillus acidophilus at 42°C for 24 h. Results: Fermentation significantly (p≤0.05) decreased pH (≥5.40–≤3.90), increased titratable acidity (≤0.55–≥0.90% lactic acid), and viscosity (≤0.65–≥0.87 Pa.S) of the soy-carrot beverages. Moisture, protein, fat, ash, carbohydrate, and energy content of unfermented beverages were 82.95– 93.95%, 2.15–2.87%, 0.42–1.21%, 0.10–0.20%, 3.21–12.55%, and 25.46–73.53 Kcal/g, respectively, while fermented beverages had 90.00–93.00%, 2.06–2.20%, 0.88–1.08%, 0.11–10.20%, 4.85–8.75%, and 36.76–52.20 Kcal/g, respectively. Total carotenoid, phenol, and DPPH radical scavenging activity varied, respectively, from 2.40–7.90, 14.81–26.59 mg tannic acid/ml, and 4.02–27.83% and were significantly (p≤0.05) highest in soy-carrot blend with carrot as major contributor. Degree of likeness of the sensory attributes for the sweetened and unfermented beverages was significantly (p≤0.05) higher than the fermented. Conclusion: Date and honey (12% Brix) can be used as sucrose alternatives in producing acceptable nutritious beverage from soymilk and carrot juice.